(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
The article provides a comprehensive examination of corruption and financial management in Uzbekistan. Through a series of detailed texts, it emphasizes the crucial role of effective state financial control, particularly led by the Accounts Chamber of the Republic of Uzbekistan, in detecting and preventing corruption crimes. The texts highlight ongoing efforts to enhance legal frameworks, methodologies, and educational programs to combat corruption. Additionally, they advocate for collaborative action among various stakeholders to address corruption comprehensively. Overall, the article underscores the importance of a coordinated approach and rigorous oversight in tackling corruption effectively.